Heat Transport Analysis for MHD Jeffery-Hamel Flow with Molybdenum Disulfide Nanoparticles: Dual Solution - Hashim; Rehman, Sohail; Afef, Kallekh; Jabeen, Iqra (Iranian journal of science and technology. Transactions of mechanical engineering, 2024)
This effort aims to explain the Jeffrey-Hamel mechanism of the nanofluid flowing via a non-parallel channel under the influence of Lorentz force. The developed model evaluates the converging/diverging channel flow and heat transfer using the mass-based nanofluid method. The mathematical modelling of nanofluid flow containing molybdenum disulfide nanoparticles and water as base liquid through a converging/diverging conduit is analyzed. The Tiwari-Das nanofluid method constitutes the basis for the current strategy. Nanoparticle masses are used in place of the volume fraction in this modelling. With the similarity solution approach, the partial differential equations for the conservation of mass, momentum, and energy are transformed into a system of ordinary differential equations. By using the bvp4c approach and the shooting method, the final governing equations are solved. Graphical reports are used to assess how developing parameters affect temperature, velocity, Nusselt number, and skin friction. It has been noted that the resistance to nanofluid flow is more pronounced when non-spherical particles are present than when particles are present. This problem shows that the form of the particles affects the rheology of a nanofluid. Moreover, for high Reynolds number values, backflow regimes develop in the diverging channel. Moreover, this modelling of the nanofluid has applications in a variety of fields, including biology. The most significant accomplishment of this study is the remarkable performance of the mass-based algorithm for heat transfer and nanofluid flow.